Service Orientation in Holonic and Multi-Agent Manufacturing Proceedings of SOHOMA 2016 - Borangiu, Theodor; Trentesaux, Damien; Thomas, André; Leitão, Paulo; Oliveira, José Barata; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The book offers an integrated vision on Cloud and HPC, Big Data, Analytics and virtualization in computing-oriented manufacturing, combining information and communication technologies, service-oriented control of holonic architectures as well as enterprise integration solutions based on SOA principles. It is structured in eight parts, each one grouping research and trends in digital manufacturing and service oriented manufacturing control: Cloud and Cyber-Physical Systems for Smart Manufacturing, Reconfigurable and Self-organized Multi-Agent Systems for Industry and Service, Sustainability Issues in Intelligent Manufacturing Systems, Holonic and Multi-agent System Design for Industry and Service, Should Intelligent Manufacturing Systems be Dependable and Safe?, Service-oriented Management and Control of Manufacturing Systems, Engineering and Human Integration in Flexible and Reconfigurable Industrial Systems,Virtualization and Simulation in Computing-oriented Industry and Service.
1 High availability cloud manufacturing system integrating distributed MES agents -- 2Classification of cyber-physical systems developments: proposition of an analysis framework -- 3Formal Modelling of Distributed Automation CPS with CP-Agnostic Software -- 4Industrial Cyber Physical Systems Supported by Distributed Advanced Data Analytics -- 5 Gap analysis on Research and Innovation for Cyber-Physical Systems in Manufacturing -- 6 Redundant and Decentralised Directory Facilitator for Resilient Plug and Produce Cyber Physical Production Systems -- 7 Multi-Agent Systems for Industry and Service -- 8 A Self-Organisation Model for Mobile Robots in Large Structure Assembly using Multi-Agent Systems -- 9 SpecifyingSelf-organising Logistics System: openness, intelligence, and decentralised control -- 10 A Generic Reconfigurable and Pluggable Material Handling System based on Genetic Algorithm -- 11 Smart condition based maintenance for a fleet of mobile entities. .
Keywords: Computational intelligence; Artificial intelligence; Industrial engineering; Production engineering; Control engineering; Robotics; Automation; Computational Intelligence; Artificial Intelligence; Industrial and Production Engineering; Control, Robotics, Automation